Neighbors help neighbors control urban mosquitoes - Johnson, Brian J. (Sci Rep, 2018)
The worldwide spread of invasive Aedes mosquitoes and arboviral disease, have renewed the pressure for effective and sustainable urban mosquito control. We report on the success of a model we are confident will usher in a new era of urban mosquito control. The key innovation is the mobilization of neighbors guided by scientific advisors, an approach we termed Citizen Action through Science (Citizen AcTS). This approach was tested in a NE US town of approximately 1,000 residential yards infested with the invasive Asian tiger mosquito, Aedes albopictus, a major nuisance arboviral vector. We report a highly significant reduction in biting pressure that was maintained over time, and establish the thresholds needed for success. The Citizen AcTS model rejects the top-down approach consistently associated with intervention failures. Instead, it works through respectful exchanges among scientists and residents that lead to trust and individual ‘buy-in’ and transferring program ownership to the community.